Practolol therapy associated with a systemic lupus erythematosus-like syndrome and an inhibitor to factor XIII. Issue 8 (August 1977) - Milner, G R; Holt, P J; Bottomley, J; Maciver, J E
Abstract : A patient is described who had an inhibitor to coagulation factor XIII associated with serum autoantibodies to certain tissues. The relationship of these abnormal findings to practolol therapy suggests that this was practolol-induced lupus erythematosus. Further investigations delineating the site of action of the inhibitor to factor XIII are reported.